Dairy farmers' business strategies in Central and Eastern Europe based on evidence from Lithuania, Poland and Slovenia. Issue 3 (3rd July 2018) - Verhees, Frans; Malak-Rawlikowska, Agata; Stalgiene, Aldona; Kuipers, Abele; Klopčič, Marija
Abstract: To evaluate market-oriented strategic decision-making by farmers in Central and Eastern Europe (CEE) farm development paths of dairy farmers in Slovenia, Poland and Lithuania were analysed. The influence of internal strengths and weaknesses, external opportunities and threats, and farmer goals on strategic choices and performance were explored. Principal component, hierarchical cluster and regression analyses were performed to test the conceptual framework. Seven strategic groups emerged with specific development paths, that is, Wait and see, Movers, Chain integrators, Specializers and Diversifiers. The latter two split into cooperative and independent groups. Maximisation of profit and sustainable farming ranked highest as farming goals. Availability of land and labour were weaknesses for all strategic groups in all countries. External opportunities and threats varied between countries and to a lesser degree between strategic groups. The Wait and see and Cooperating diversifier groups gave less optimistic scores than other strategic groups. The attitudes of CEE farmers towards the market and future Common Agricultural Policy remain more negative than those of a group of Western European farmers. The results of this study confirm that internal strengths and weaknesses, external opportunities and threats, together with farmers' goals and strategies influence farmer performance, but independently of each other. Strategies do not appear to be a mediating variable between the internal and external environment of the farm and the performance of the farm. Policy makers, companies and extension workers should take the heterogeneity in strategic development into account when dealing with these and similar groups of farms.